Hubungan Tradisi Nadran Gunungjati dengan Tingkat Pengendalian Konflik pada Kasus Tawuran Masyarakat Desa Sirnabaya dan Desa Purwawinangun - Hofifah Indah Faramita; Hanifaty Fadhilah; Alfi; Hana Indriana (Jurnal Ekologi, Masyarakat dan Sains, 2022)
Sirnabaya and Purwawinangun villages are located in the Gunungjati area, Cirebon Regency, which is an area with a strong tradition. One of them is the Nadran tradition which is carried out as a form of community gratitude for the produce of the earth and the sea. However, the two villages are known for their brutal fighting conflicts. Therefore, this study aims to determine the relationship between traditional values ??and the level of conflict control. The research was conducted with quantitative supported by qualitative methods. The research instrument was a questionnaire to collect data from 40 respondents. In-depth interviews were conducted with 10 informants. Data analysis was performed using Spearman correlation. The results showed that there was a significant relationship between the Nadran tradition and the level of conflict control that occurred between Sirnabaya and Purwawinangun villages. Even though the community knows and applies the noble values ??of the Nadran tradition, the community tends to be involved in conflict. This happens because individuals lose their identity when in a crowd or are called deindividuation symptoms. This research is expected to be a consideration for the committee and the government in regulating the Nadran implementation system so that conflicts can be minimized.